My father, the pornographer ebook A memoir. - Offutt, Chris (2016)
PUBLISHERS WEEKLY BEST BOOK OF THE YEAR After inheriting 400 novels of pornography written by his father in the 1970s and '80s, critically acclaimed author Chris Offutt sets out to make sense of a complicated father-son relationship in this carefully observed, beautifully written memoir. "Chris Offutt owns one of the finest, surest prose styles around, ready and able to convey the hardest truth without flinching. Now Offutt enters the darkest and most mysterious of places—the cave of a monstrous enigma named Andrew J. Offutt—armed with nothing but his own restless curiosity. Spoiler alert: He makes it out alive, walking into the daylight to bring us a deeper, funnier, more tender and more heartbroken truth—and his masterpiece." —Michael Chabon When Andrew Offutt died, his son, Chris, inherited a desk, a rifle, and eighteen hundred pounds of pornographic fiction. Andrew had been considered the "king of twentieth-century smut," with a writing career that began as a strategy to pay for his son's orthodontic needs and soon took on a life of its own, peaking during the 1970s when the commercial popularity of the erotic novel reached its height. With his dutiful wife serving as typist, Andrew wrote from their home in the Kentucky hills, locked away in an office no one dared intrude upon. In this fashion he wrote more than four hundred novels, including pirate porn, ghost porn, zombie porn, and secret agent porn. The more he wrote, the more intense his ambition became and the more difficult it was for his children to be part of his world. Over the long summer of 2013, Chris returned to his hometown to help his widowed mother move out of his childhood home. As he began to examine his father's manuscripts and memorabilia, journals, and letters, he realized he finally had an opportunity to gain insight into the difficult, mercurial, sometimes cruel man he'd loved and feared in equal measure. Only in his father's absence could he truly make sense of the man and his legacy. In My Father, the Pornographer , Offutt takes us on the journey with him, reading his father's prodigious literary output as both a critic and as a son seeking answers. This is a book about the life of a working writer who supports his family solely by the output of his typewriter; it's about the awful psychic burdens one generation unthinkingly passes along to the next; and it's about growing up in the Appalachian hills with a pack of fearless boys riding bicycles through the woods, happy and free.